Polyethyleneglycol/silver functionalized Reduced graphene oxide aerogel for environmental application - Kumari, G. Vanitha; Asha, S.; Ananth, A. Nimrodh; Rajan, M. A. Jothi; Mathavan, T. (62nd Dae Solid State Physics Symposium, 2018)
Polyethylene glycol (PEG)/Silver (Ag) functionalized reduced graphene oxide aerogel (RGOA) was synthesized. PEG/Ag decorated reduced graphene oxide aerogel was characterized using XRD, Raman spectroscopy, Fourier transform infrared spectroscopy (FT-IR). The surface morphology of PEG/Ag/RGOA was analyzed using scanning electron microscope. The non-covalent interaction between reduced graphene oxide layers and the interaction between PEG and Ag on RGOA were studied by FT-IR spectra. It was observed that the interaction between Ag and PEG could enhance the properties of RGOA. Methyl Orange (MO) dye degradation was observed from UV-Vis Spectra. The process was studied by monitoring the simultaneous decrease in the height of UV-Vis absorption peak of dye solution. The results show that PEG/RGOA and PEG/Ag/RGOA are an efficient catalyst for dye degradation.